The effect of Beta-amino Butyric Acid in Levels of Interleukin4 & Interleukin 10, Complement Proteins C3 & C4 and Immunoglobin IgM in Males Rats Sprague Dawley Infected with Pseudomonas aeruginosa - Zainab Makki Sagheer1 Mohammad Abas Jasim1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
B–amino butyric acid (BABA) non protein amino acid has effect on some immunological parameters of male rats Sprague Dawley species infected with pseudomonas aeruginosa. this study include 25 animal divided into five groups A, B, C, D and E each group contain five animals, A, B and C groups injected with three concentration of amino acid solution (25 mg\ml, 50 mg\ml and 75 mg\ml) with dose (0.2 g\ kg, 0.4g\kg and 0.6 g\kg) respectively, intra peritoneal weekly for six weeks, group D (first control group) and E (second control group) injected with normal saline. At the fifth week the four groups A, B, C and D exposed to pseudomonas aeruginosa, while group E did not exposed to infections after the termination of period of treatment, The blood samples were collected to do the immunological tests, the statistical analysis P<0.05 results showed BABA did not enhance sensitivity through measuring interleukin IL4, and significant increase of IL10 and complement protein C4, while BABA didn’t have a negative effect on the complement protein C3 activation and increase the level of immunoglobulin IgM.